Holocene Environmental Change in the Frobisher Bay Area, Baffin Island, N.W.T.: Deglaciation, Emergence, and the Sequence of Vegetation and Climate - Jacobs, J.; Mode, W.; Squires, C.; Miller, G. (Géographie physique et Quaternaire, 1985)
ABSTRACTThe late-glacial and Holocene paleoenvironmental sequence for the Frobisher Bay area is outlined using glacial, sea level, and palynological evidence. A rapid retreat of ice from the late Foxe glacial maximum in the lower part of the bay after 11,000 BP was followed by a series of stillstands or minor readvances between ca. 8500 and 7000 BP and possibly later, before the final disappearance of the inland ice centred near Amadjuak Lake. Lithostratigraphy of three buried organic sections which together represent deposition occurring over the period from 5500 to 400 BP indicates a change from a relatively warm, moist environment before 5500 BP to neoglacial conditions, with the coldest phases centred around 5000, 2700, 1200 BP and probably sometime after 400 radiocarbon years BP. As evidenced by peat growth and pollen data, milder, wetter conditions prevailed from 4500 to 3000 BP and again from ca. 2600 to 1800 BP. Peat growth and soil organic fractions point to lesser mild intervals ca. 900 BP and 400 BP, but these are not apparent in the pollen assemblage. The pollen record does not extend to the last four centuries; however, lichenometric studies of neoglacial moraines by DOWDESWELL (1984) show that the maximum late Holocene advance of glaciers in the area occurred within the last century. Modern pollen samples indicate that the present vegetation of the inner Frobisher Bay area is comparable to that of the milder intervals of the late Holocene.